Synthesis of camphene by α-pinene isomerization using acid nano titanium dioxide catalysts. (20th March 2023) - Wu, Wenxing; Chen, Yanqi; Liu, Naiwang; Shi, Li; Meng, Xuan
Abstract : In this study, we investigated the application of an acidic titanium dioxide catalyst in fixed bed reactors for the isomerization of α-pinenes. Abstract : In this work, several acid-activated catalysts were tested in the isomerization reaction of α-pinene to obtain camphene, a very high-value-added chemical. Titanium-based precursors (H2 TiO3 powder, TiO2 powder, and TiO2 nanopowder) were activated using a variety of acids to prepare acid-activated catalysts, and the catalysts were characterized by XRD, SEM, IR, Py-IR, and BET methods to determine the structure–activity relationship between the catalyst acidity, pore structure and catalyst isomerization performance. The results showed that the catalyst surface area and total acidity increased with the acid activation of precursors. The conditions that affect the reactions were studied, including the type of acid treatment and titanium-based precursor used for activation, reaction temperature, and weight hourly space velocity. Preliminary studies showed that the most active catalyst was the TiO2 nanopowder activated by hydrochloric acid. Under optimized conditions, α-pinene was completely converted with high selectivity (63.96%) towards camphene, which has a higher commercial value. The variation law of product distribution with time was also studied in order to investigate the isomerization mechanism of α-pinene. A catalyst regeneration experiment demonstrates the exceptional stability and regenerative capabilities of the catalyst.